Weinbau, Obstbau und Sozialbrache am Oberen Mittelrhein - Dege, Eckart (ERDKUNDE, 1973)
In this study the interrelationship between the changing agricultural landscape and the socio-economic development of the population which forms this landscape are analyzed, using two former wine-growing villages on the upper middle Rhine as an example. Until the second half of the last century the economic and social structure of the studied villages was determined by wine-growing, which supplied the population with cash, whereas the cultivation of the fields provided the necessary food. It was impossible to give up wine-growing, although it was often hit by crises, because the population-with no source of income outside of agriculture-had to rely on its returns. A change to a less intensive culture was impossible because, as a consequence of the century-old practice of dividing the land equally among all children, the sice of the farms had become extremely small. At the end of the last century this situation was altered by the changes in the socio-economic structure of the population caused by the industrial revolution. Now many former wine-growers found their main income in the developing industry. At first they cultivated their vineyards as a supplementary source of income, but soon changed to fruit-growing (esp. cherries) as a new, promising culture, after wine-growing was hit by another severe crisis (1909 1916). So in less than a decade the former wine-growing landscape turned into a fruit-growing landscape. In the course of the following socio-economic development (which did not proceed in a straight line, but in waves according to the general economic development) such a large proportion of the population turned their backs on agriculture that after a last (cherry and strawberry) boom in the 50's, the fruit-growing landscape is rapidly turning into one characterized by social fallow. How definitely the population has broken with agriculture can be traced (e.g. by studying the changes in land prices) in their attitude toward their land, which was found to be the guiding factor in the development of the agricultural landscape.